From Asymptomatic Flatfoot to Progressive Collapsing Foot Deformity: Peritalar Subluxation Is the Main Driver of Symptoms - Cesar de Cesar Netto MD, PhD; Nacime Salomao Barbachan Mansur MD, PhD; Grayson M. Talaski; Andrew Behrens BS; Kepler A.M. Carvalho MD; Eli Schmidt BS; Ryan Jasper MS; Kevin Dibbern PhD; François Lintz MD, PhD; Scott J. Ellis MD; Donald D. Anderson PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Ankle Introduction/Purpose: Having a flatfoot can be normal. Having a flatfoot that is getting worse is not normal. But how does that happen? What leads to symptoms? Those questions are yet to be answered in the literature. In this prospective comparative study, we recruited patients with asymptomatic flatfoot and controls with normal foot alignment and compared to patients with Progressive Collapsing Foot Deformity (PCFD). We hypothesized that measurements of foot deformity and collapse – Class A for hindfoot valgus, Class B for Midfoot/Forefoot abduction, and Class C for longitudinal arch collapse - would be progressively more pronounced in controls, asymptomatic flatfoot, and PCFD patients. However, only symptomatic PCFD patients would demonstrate signs of Peritalar Subluxation (PTS) or Class D deformity. Methods: In this IRB-approved study, we prospectively recruited adult volunteers with normal foot alignment and with flatfoot morphotype and no history of foot/ankle pain, major injury, or surgeries. We included a total of 88 controls (98 feet) and 66 asymptomatic flatfoot patients (132 feet), as well as a retrospective cohort of 306 symptomatic PCFD patients (311 feet). All patients underwent bilateral Weightbearing Computed Tomography (WBCT). Measurements of alignment and collapse were compared between the groups. Measurements included: Hindfoot Moment Arm (HMA) (Class A deformity); Talonavicular Coverage Angle (TCA) (Class B); Forefoot Arch Angle (FAA) (Class C); as well as distance and coverage maps of the sinus tarsi, anterior, middle, and posterior subtalar joint facets, as markers of PTS (Class D). Data was compared using paired T-tests/Wilcoxon. A multivariate nominal regression analysis and a partition predictive model were utilized to identify measurements influencing the presence of symptoms. P-values < 0.05 were considered significant. Results: Class A, B, and C measurements were significantly and progressively more pronounced in asymptomatic flatfoot and PCFD patients when compared to controls (p-values < 0.0001). However, PTS measurements were similar in control and asymptomatic patients and only significantly more pronounced in symptomatic PCFD patients. PCFD patients had respectively 12.7% and 14.3% less posterior and middle facets coverage and 19.6% increased coverage of the sinus tarsi when compared to asymptomatic flatfoot patients (P-values < 0.0001). Multivariate analysis demonstrated that posterior facet and sinus tarsi coverages, minimum sinus tarsi distances, FAA, and HMA were found to significantly influence the presence of symptoms (p < 0.0001). The partition predictive model demonstrated that minimum values of sinus tarsi distance lower than 1.9mm would lead to 89% chances of a patient having symptomatic PCFD. Conclusion: In this prospective comparative study, we aimed to investigate the differences between a normally aligned foot, an asymptomatic flatfoot, and a symptomatic Progressive Collapsing Foot Deformity, searching for drivers of symptoms. We found that when compared to controls, Class A (hindfoot valgus), B (midfoot/forefoot abduction), and C (arch collapse) measurements were progressively and significantly more pronounced in asymptomatic flatfoot and PCFD patients. However, Class D Deformity (Peritalar Subluxation), including sinus tarsi and subtalar joint coverage, was found to be similar in controls and asymptomatic flatfoot, but significantly more pronounced in PCFD patients, potentially representing the primary driver of symptoms.